2000
DOI: 10.1136/oem.57.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated dibenzo-p-dioxin and dibenzofuran concentrations in the serum samples of workers at continuously burning municipal waste incinerators in Japan

Abstract: Objectives-To find whether concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in serum increased in workers at municipal incinerators that burn continuously. Methods-30 Workers employed at three municipal waste incineration plants (incinerator workers) and 30 control workers were studied. The incinerator workers had worn dust masks or airline masks during the periodic repair work inside the incinerators. Previous job, dietary habit, smoking habit, distance fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 25 publications
5
26
1
Order By: Relevance
“…They found the content of heptachlorinated dibenzofurans and dibenzodioxins were several orders of magnitude greater than other total congeners (tetra, penta, hexa, octa); however, congener-specific data within the hepta class were not reported. Similar findings have been found in Japanese incinerator workers (Kumagai et al 2000(Kumagai et al , 2002. Our results demonstrating differences for the two hepta congeners were not anticipated but are consistent with other published data and suggest that these analytes may be useful for detecting exposures to burning plastics containing chlorine.…”
Section: Discussionsupporting
confidence: 92%
“…They found the content of heptachlorinated dibenzofurans and dibenzodioxins were several orders of magnitude greater than other total congeners (tetra, penta, hexa, octa); however, congener-specific data within the hepta class were not reported. Similar findings have been found in Japanese incinerator workers (Kumagai et al 2000(Kumagai et al , 2002. Our results demonstrating differences for the two hepta congeners were not anticipated but are consistent with other published data and suggest that these analytes may be useful for detecting exposures to burning plastics containing chlorine.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, Tepper et al (1997) found serum PCDD/F levels of 18.1 pg I-TEQ/g a Only nine workers showed 1-HP levels above the detection limit lipid (low exposure) and 21.2 pg I-TEQ/g lipid (high exposure) in pulp and paper mill workers compared with a concentration of 19.1 pg I-TEQ/g lipid for community residents. Recently, Kumagai et al (2000) did not ®nd signi®cant dierences in the serum mean concentrations of PCDD/Fs in Japanese MWI workers (19.2±28.8 pg I-TEQ/g lipid) and control subjects (22.9±24.5 pg I-TEQ/ g lipid).…”
Section: Discussionmentioning
confidence: 98%
“…Average TEQ concentrations of t-PCDD/Fs in the blood samples of general population in Europe are 14-43 pg I-TEQ/g lipid, 19-27 pg I-TEQ/g lipid in North America, 20-22 pg I-TEQ/g lipid in Japan 33) . Twelve PCB isomer concentrations are calculated as TEQ calculated by I-TEFs suggested by WHO in 1997 34) .…”
Section: Exposure Assessment Of Pcdd/fs Homologue In Residents Near Tmentioning
confidence: 99%